Pengaruh Kualitas Pelayanan dan Harga Produk terhadap Kepuasan Pelanggan di E-commerce Shopee - Reisya Aulia Anhar; Keysha Azahra Ramadhani; Omar Mochtar Andela (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to analyze the effect of service quality and product price on customer satisfaction at Shopee. Service quality, which includes ease of access, transaction security, delivery speed, and other supporting features, is an important factor in creating customer satisfaction. Meanwhile, competitive product prices, discounts, and promotions are also the main considerations for consumers in choosing an e-commerce platform. The results of the study show that service quality and price have a significant effect on customer satisfaction. Good service quality can improve customer experience, while competitive prices increase customer attraction to shop.